Error Analysis of German Imperative Sentence Formation (Imperativsatz) - Jenita Bulawan; Muh Anwar; Ernawati Ernawati (Universitas Negeri Makassar, 2026)
Abstract. This study aims to obtain data on the types of student errors in forming German imperative sentences (Imperativsatz) and strategies for overcoming errors that occur in the formation of German imperative sentences (Imperativsatz). This research is a qualitative study with an interpretive analytical approach. The data in this study are imperative sentences (Imperativsatz) written by students in the forms of du-Form, ihr-Form, and Sie-Form. The data sources in this research are 34 students from class XII.9 of SMA Negeri 12 Makassar. Written tests were used to obtain the data. The data were analyzed using the error analysis method proposed by Ellis in Tarigan. The results of the data analysis show that the most frequent errors made by students were in imperative sentences (Imperativsatz) in the du-Form with 154 errors or a percentage of 37.47%, in the Sie-Form with 138 errors or a percentage of 33.57%, and in the ihr-Form with 119 errors or a percentage of 28.96%. Furthermore, the overall average score of errors in forming German imperative sentences (Imperativsatz) made by students of class XII.9 at SMA Negeri 12 Makassar falls into the high category at 48.35%.Keyword: Error Analysis, Sentence Formation, Imperative Sentences, German Language